GROUP STATE ROUTING PROTOCOL (MYCELIA): НОВА МОДЕЛЬ КООРДИНАЦІЇ РО-ЗПОДІЛЕНОЇ МЕРЕЖІ - Toliupa , Serhii; Kotov, Maksym (Science-based technologies, 2026)
The following article is describing a new model of managing secure communication channels in a distributed environment with the aim of minimizing cryptographic windows and attack vectors based on traffic correlation analysis. In the contemporary world of digital interconnection, having the ability to preserve the confidentiality of the data exchange between multiple peers gains significant importance. A secure communication channel must provide meaningful guarantees of confidentiality, integrity, and availability of the data that is being transmitted as well as ensure minimized latencies due to security mechanism overhead. Existing solutions centered around Virtual Private Networks, mesh-like topologies, and relays share limitations in their ability to avoid traffic concentration points such as entry and public-facing nodes. Thus, it is possible for cryptanalysts to correlate traffic in some cases and potentially compromise the secrecy of communication. Hence, the proposed model aims to avoid such concentration points during traffic transmission by leveraging the capabilities of group routing and decentralized cluster state coordination based on the Replica State Discovery Protocol. A comparative analysis has been conducted to illustrate the difference in communication topologies between existing solutions and the proposed protocol. At the basis of this research is a theoretical analysis of the proposed model’s topology and methods used to facilitate the secure channels’ creation and traffic relay mechanisms. Mathematical modeling has been leveraged to formally describe the properties of the proposed protocol to further facilitate its integration into the modern communication systems. As a result, a model for a distributed management of secure communication channels has been developed and analyzed that reduces the likelihood of attacks based on traffic correlation and thus improves the confidentiality characteristics of the connection between participating peers. A new path routing method based on relay groups has been proposed as well as the traffic dispersion principles related to the outgoing traffic from the mesh network. Secondly, a method of distributed traffic dispersion and coordination has been developed based on the RSDP that allows for avoiding concentration of authority and thus lays the foundation for the decentralized version of building secure communication channels